2015
DOI: 10.3389/fmats.2015.00042
|View full text |Cite
|
Sign up to set email alerts
|

Laser Patterning of Non-Linear Optical Bi2ZnB2O7 Crystal Lines in Glass

Abstract: Bi2O3-based glasses are very attractive from the viewpoints of low-melting, high refractive index and crystallization, and the research on their glasses and glass-ceramics is at the frontiers of glass science and technology. Nonlinear optical Bi2ZnB2O7 crystal lines with a high orientation were patterned in 3Sm2O3-30.3Bi2O3-33.3ZnO-33.3B2O3 glass by using a laser-induced crystallization technique. It was confirmed from transmission electron microscope observations that crystals were formed in the inside of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The 12 h-sintered pattern reveals additional crystalline phases-Bi 2 ZnB 2 O 7 and an unknown phase. These two crystalline phases are also found in literature about Bi 2 O 3 -based glasses [58][59][60][61][62][63][64][65][66]. On the other hand, it was found that all the 30 min-sintered glasses made from the coarse powders (d…”
supporting
confidence: 78%
“…The 12 h-sintered pattern reveals additional crystalline phases-Bi 2 ZnB 2 O 7 and an unknown phase. These two crystalline phases are also found in literature about Bi 2 O 3 -based glasses [58][59][60][61][62][63][64][65][66]. On the other hand, it was found that all the 30 min-sintered glasses made from the coarse powders (d…”
supporting
confidence: 78%
“…Considering crystal growth kinetics in glass, low laser scanning speed, i.e., keeping high temperature for long period, would be favorable for crystal growth. Of course, however, optimal laser irradiation condition (optimal laser power and scanning speed) is required for the pattering of homogeneous crystal lines (Honma et al, 2005;Inoue et al, 2015).…”
Section: Nucleation and Homo-epitaxial Crystal Growth In Crossing Linesmentioning
confidence: 99%
“…Spatially selected patterning of crystals in glasses by laser irradiation, i.e., laser-induced crystallization, is also extremely attractive, which is a new method for the design and control of the crystallization of glasses and also opens a new door in the study of nucleation and crystal growth in glasses Komatsu and Honma, 2013;Inoue et al, 2015;Komatsu, 2015). In the laser-induced crystallization, a steep temperature gradient is created in the laser-irradiated local region, and such a steep temperature gradient is moved along laser scanning direction, consequently providing the patterning of crystals with high orientation.…”
Section: Introductionmentioning
confidence: 99%